Hedgehog Pathway Alterations Downstream of Patched-1 Are Common in Infundibulocystic Basal Cell Carcinoma. (April 2021) - Russell-Goldman, Eleanor; MacConaill, Laura; Hanna, John
Abstract : Abstract: The infundibulocystic variant of basal cell carcinoma (BCC) is characterized histologically by anastamosing strands of basaloid epithelium with associated small infundibular-type cysts. Since its first description in 1987, this rare entity has generated considerable controversy with some authors classifying it as a benign follicular neoplasm rather than a BCC subtype. Prior studies aiming to settle this issue using immunohistochemical analysis reached opposite conclusions. The defining feature of BCC is activation of the Hedgehog signaling pathway, and mutations in Patched-1 (PTCH1) are the most common molecular finding in both sporadic and inherited forms of BCC. Mutations in other downstream components including Smoothened (SMO) and Suppressor of Fused (SUFU) also occur, but are much less common. Here, we report a molecular genetic analysis of a small series of infundibulocystic BCC using a next-generation DNA sequencing platform. All 4 cases harbored mutations or other genetic alterations in components of the Hedgehog pathway, supporting the classification of this entity as a BCC variant. Interestingly, these tumors were enriched for genetic alterations downstream of PTCH1, involving SUFU, SMO, GLI1, and GLI2. This observation was of particular interest given that rare kindreds of the Multiple Hereditary Infundibulocystic BCC syndrome (MHIBCC), which is related, but possibly distinct from the nevoid BCC syndrome, harbored mutations in SUFU. Our results support the classification of the infundibulocystic variant as a subtype of BCC, and suggest that the level at which genetic alterations occur within the Hedgehog pathway may be an important determinant of the morphologic features in BCC.